Customer Satisfaction In Mobile Payment System: Finding From Indonesia - Rian Hermawan; Mohamad Rizan; Agung Wahyu Handaru (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2020)
This research was conducted to produce a customer loyalty model in the mobile payment business in Indonesia. The mobile payment industry is currently in a period of rapid growth. Mobile payments are a vast need felt by consumers, especially in urban areas with good quality internet networks. Even though it is online, it still requires good customer service and can provide user satisfaction with this application. In this mobile payment business competition, the Link Aja company tries to compete with several platforms with several weaknesses in its business strategy. To achieve the research objectives, a sample selection of 200 users of the Link Aja mobile platform who live in Jakarta was selected. Non-probability sampling techniques are used to facilitate the collection of primary data needed to analyze the structural equation models used to test the hypothesis. The results of hypothesis testing reveal that service quality, promotion, and customer satisfaction have a positive impact on the level of customer loyalty of the Link Aja platform. Besides, customer satisfaction itself is influenced by the quality of service and promotions carried out by the Link Aja platform. The recommendation for the Link Aja platform is to immediately improve the application to make it easier to use and provide more cashback promotions for its users. Keywords: Service Quality, Promotion, Customer Satisfaction, Customer Loyalty.